Forensic Monitoring Project Report: Sanski Most Cememtery Exhumations Republika Srpska Commission on Missing and Tracing - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: York, Heather From 19-22 October 1998 the Republika Srpska Commission on Missing and Tracing recovered 69 sets of human remains from a cemetery east of Sanski Most. Based on witness information, the R.S. Commission expected to find the remains of 75-100 soldiers and civilians who died during or shortly after the fall of Sanski Most in 1995 and were buried by Bosnian Serbs. Place of Exhumation: Sanski Most Date of Exhumation: 19-22 October 1998 Minimum Number of Exhumed Individuals: 069